STRATEGI PENGEMBANGAN MINAWISATA BAHARI KATEGORI KERAMBA JARING APUNG (KJA) BERBASIS KESESUAIAN DAN DAYA DUKUNG DI PERAIRAN NEGERI AMAHAI KABUPATEN MALUKU TENGAH - Matahurilla, A C D; Khouw, A S; Abrahamsz, J (Departement of Aquatic Resources Management, Fisheries and Marine Science Faculty, Pattimura University, 2019)
The potential of resources and the development of environmental services have not been utilized optimally so that an effort to integrate management in terms of ecology and economy based on tourism fish farming is needed. The research to analyse suitability and carryng capacity as well as to formulate the strategy and development priority for marine fisheries tourism of floating cage. This research was conducted on November 2017 to February 2018 at Amahai coastal water. Primary data was collected through direct observation at 10 stations while secondary data was obtained from literature. Suitability was analysed by using region suitability matrix while carrying capacity was calculated based on PPLKPL-KLH/FPIK-IPB. Arrangement of strategic factors was based on SWOT matrix and then analysed by using TOWS while priority of development strategy was analysed by using Analytical Hierarchy Process. The result showed that all stations were suitable for marine fisheries tourirsm of floating cage with the percentage ranged from 95.09% (stations 6, 8, 9) to 100% (stations 1-5, 7, 10). However, based on carrying capacity, there were only six groups of floating cage with total area of 0.45 ha for each group. There were 14 strategies and nine priorities to develop marine fisheries tourism of floating cage in the region of Amahai. ABSTRAK Potensi sumberdaya dan pengembangan jasa lingkungan belumlah dimanfaatkan secara optimal sehingga diperlukan suatu upaya integrasi pengelolaan dari segi ekologi dan ekonomi berbasis minawisata keramba jaringa apung (KJA). Tujuan penelitian yaitu menganalisis kesesuaian kawasan, daya dukung kawasan, serta menformulasikan strategi dan prioritas pengembangan untuk kawasan minawisata bahari kategori KJA di Negeri Amahai. Penelitian ini berlangsung pada bulan November 2017-Februari 2018 di pesisir Negeri Amahai. Pengumpulan data berupa data primer dan data sekunder. Analisis data untuk kesesuaian menggunakan matriks kesesuaian kawasan minawisata bahari kategori KJA, sedangkan perhitungan daya dukung merujuk pada PPLKPL-KLH/FPIK-IPB. Penyusunan faktor-faktor strategis menggunakan matriks SWOT, kemudian dianalisis dengan TOWS, sedangkan untuk menyusun prioritas strategi pengembangan menggunakan analisis AHP. Hasil perhitungan menunjukkan bahwa nilai indeks kesesuaian minawisata bahari kategori KJA pada stasiun 1 sampai 5,7 dan 10 sebesar 100% (sesuai), sedangkan pada stasiun 6, 8, dan 9 sebesar 95,09% (sesuai). Berdasarkan daya dukung kawasan minawisata bahari kategori KJA diperoleh sebanyak 6 kelompok dengan areal 0,45 ha. Terdapat 14 strategi dan 9 prioritas untuk mengembangkan kawasan minawisata bahari kategori KJA di Negeri Amahai. Kata Kunci: Minawisata bahari, keramba jaring apung, kesesuaian, daya dukung, Amahai